Second generation, arginine-rich (R-X `-R)(4)-type cell-penetrating alpha-omega-alpha-peptides with constrained, chiral omega-amino acids (X `) for enhanced cargo delivery into cells - Patil, Kiran M.; Naik, Rangeetha J.; Vij, Manika; Yadav, Amit K.; Kumar, Vaijayanti A.; Ganguli, Munia; Fernandes, Moneesha (Bioorganic & Medicinal Chemistry Letters, 2014)
The syntheses of novel N-aminoalkyl proline-derived spacers (X') in polycationic (R-X'-R)-motif cell-penetrating alpha-omega-alpha-peptides are described as improved molecular transporters and their structural features studied by CD. FACS analysis shows enhanced cellular uptake and confocal microscopy indicates predominantly cytoplasmic localization. The oligomers are efficient at transporting pDNA into cells. The chirality together with the hydrophobicity and flexibility derived from the spacer chain are found to have marked influence on the cell-penetrating and cargo delivery properties of the cell-penetrating peptides (CPPs). The peptides containing N-(3-aminopropyl)-D-proline spacers are found to be the best at cell penetration and cargo delivery in the present study. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: (R-X-R)-motif; alpha-omega-alpha-Peptide; Cell-penetrating peptide; Constrained chiral amino acid; Peptidomimetics

(R-X-R)(4)-Motif peptides containing conformationally constrained cyclohexane-derived spacers: effect on cellular uptake - Bhosle, Govind S.; Fernandes, Moneesha (ChemMedChem, 2017)
Arginine-rich peptides having the (R-X-R) n motif are among the most effective cell-penetrating peptides (CPPs). Herein we report a several-fold increase in the efficacy of such CPPs if the linear flexible spacer (-X-) in the (R-X-R) motif is replaced by constrained cyclic 1,4-substituted-cyclohexane-derived spacers. Internalization of these oligomers in mammalian cell lines was found to be an energy-dependent process. Incorporation of these constrained, non-proteinogenic amino acid spacers in the CPPs is shown to enhance their proteolytic stability.
Keywords: (R-X-R)-motif; cell-penetrating peptides; cellular uptake; protease stability